2012
DOI: 10.1534/g3.112.002840
|View full text |Cite
|
Sign up to set email alerts
|

A Genome-Wide Screen Identifies Genes That Affect Somatic Homolog Pairing inDrosophila

Abstract: In Drosophila and other Dipterans, homologous chromosomes are in close contact in virtually all nuclei, a phenomenon known as somatic homolog pairing. Although homolog pairing has been recognized for over a century, relatively little is known about its regulation. We performed a genome-wide RNAi-based screen that monitored the X-specific localization of the male-specific lethal (MSL) complex, and we identified 59 candidate genes whose knockdown via RNAi causes a change in the pattern of MSL staining that is co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
43
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 67 publications
6
43
0
1
Order By: Relevance
“…Thus, our evidence suggests that the role of H4K20 methylation in MSL recruitment and exclusion from chromatin is quite specific for H4K20me1 and H4K20me3, respectively. Consistent with a role for PR-SET7 and H4K20me1 in MSL targeting, a recent study in flies demonstrated that loss of PR-SET7 leads to perturbations in MSL localization on the male X chromosome (42).…”
Section: Discussionmentioning
confidence: 55%
“…Thus, our evidence suggests that the role of H4K20 methylation in MSL recruitment and exclusion from chromatin is quite specific for H4K20me1 and H4K20me3, respectively. Consistent with a role for PR-SET7 and H4K20me1 in MSL targeting, a recent study in flies demonstrated that loss of PR-SET7 leads to perturbations in MSL localization on the male X chromosome (42).…”
Section: Discussionmentioning
confidence: 55%
“…(Also Shachar et al[62], which describes another high-throughput pipeline.) The third screen also used cell culture, in this case, assaying pairing of the X chromosome through the localization of the X-enriched MSL dosage compensation machinery [63]. …”
Section: Identification Of Pairing and Anti-pairing Factors By High-tmentioning
confidence: 99%
“…Excitingly, many of these genes were also identified by MSL localization [63], implying that these genes regulate the pairing of whole chromosomes. Consistent with this conclusion, many of these genes were also found to influence pairing at euchromatic regions by FISH [30].…”
Section: Identification Of Pairing and Anti-pairing Factors By High-tmentioning
confidence: 99%
“…transvection, have been identified, and may function differently in different cell types (Hartl et al 2008;Bateman et al 2012b;Joyce et al 2012). Finally, data based on DNA-FISH show high levels of somatic homolog pairing in third instar larvae, but lower levels during embryogenesis, which would likely negatively impact transvection in early tissues (Fung et al 1998).…”
Section: Factors Other Than Enhancer Strength Influence Transvectionmentioning
confidence: 99%